A mechanism to prevent production of reactive oxygen species by Escherichia coli respiratory complex I - Marius Schulte (Nature Portfolio, 2019)
Respiratory complex I plays a central role in cellular energy metabolism coupling NADH oxidation to proton translocation. Here, the authors report the structure of the electron input part of Aquifex aeolicus complex I at up to 1.8 Å resolution with bound substrates in the reduced and oxidized states.